A DESCRIPTIVE STUDY ON TEACHER-LEARNER INTERACTION IN SPEAKING CLASS AT THE FIRST YEAR OF SMP N 2 BENDOSARISUKOHARJO IN 2010/2011 ACADEMIC YEAR - WAHYUNINGSIH, LINA (2011)
This research aims at describing teacher-learner interaction in speaking class, the strategies of the teacher to elicit interaction, and the problems faced by the teacher and learner on interaction in speaking class. This research uses descriptive qualitative research. The writer gets the data of this research from event, informant, and document. The events in this research are all of the activities occurred in the speaking class. Informants are the English teacher and the students of SMP N 2 Bendosari. Documents are all of the written information related to the interaction in speaking class. The method of collecting data is observation, interview, and data analysis of interaction in speaking class. The result of the study shows that teacher-learner interaction in speaking class of SMP N 2 Bendosari is good but the interaction is dominated by the teacher. The language functions used in their interaction are praise or encourage, ask question, giving direction, lecturing, students' response,and silence or confusion. The method of speaking classroom interaction is Flanders' Interaction Analysis System (FIAS). There are two types of interaction occurred in speaking class namely; learner instruction interaction and learner-learner interaction.The characteristic of teacher talk are teacher's language modification, teacher's question and teacher's feedback. The characteristic of student talk are students' pause and students' fluency disorder.